Secure Pesticide Storage: Security and Safety-promoting Features of Pesticide Storage Facilities - Thomas W. Dean (EDIS)
This document describes nine features that specifically promote pesticide storage facility security and safety. This document is Fact Sheet PI-32, part of a series from the Pesticide Information Office, Food Science and Human Nutrition Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: April 2004. Revised: November 2004.